Perfil electroforético del suero sanguíneo en caninos diagnosticados con ehrlichiosis - Chalco Ortega, Adriana Mayte (Machala : Universidad Técnica de Machala, 2021)
Canine ehrlichiosis is a tick-borne disease caused by several species of rickettsia (Rickettsiae) belonging to the genus Ehrlichia, including E. canis, E. ewingii, and E. chaffeensis. Because the disease is generally asymptomatic (subclinical phase), it constitutes an important epidemiological factor for the spread of the infection. There are several techniques for the diagnosis of Ehrlichiosis, that include indirect immunofluorescence (IFI), ELISA, direct smear, solid layer chromatography and the polymerase chain reaction (PCR), being the ELISA method and the direct smear, the most used. This work raises the possibility of using a variation of the gel electrophoresis technique with easily obtainable buffers that have a good resolution of serum protein fractions for the diagnosis of canine Ehrlichiosis, in combination with the determination of other parameters such as the Hematocrit and the average diameter of the erythrocytes. The analysis of 31 dogs that came to the UTMACH Veterinary Specialties Teaching Clinic, which underwent a rapid test with the SensPERT Ehrlichia canis Ab commercial kit, allowed the identification of 19 seropositive and 12 seronegative animals. The white layer smear analysis only confirmed the presence of morulae in 31.82% of the seropositive individuals. The seropositive dogs presented lower hematocrit values ​​and a marked macrocytosis evidenced from the analysis of the mean diameter of the erythrocytes. The concentration of total proteins and total globulins was higher in seropositive dogs, whereas for the Albumin concentration quantified by the Bromocresol Green method, no statistical differences were detected between seropositive and seronegative dog groups. Agarose gel electrophoresis and subsequent analysis of the respective densitograms allowed to establish hypoalbuminemia and evident increases in the fraction of gamma globulins in seropositive canines. When the Albumin fraction was analyzed by the densitometric data obtained from the electrophoretic fractionation in agarose gel, the statistical differences revealing a hypoalbuminemic condition in seropositive dogs. The albumin/globulin ratio (A/G) from the data obtained by colorimetry was higher in seropositive dogs, whereas the densitometric analysis of the electrophoretic runs revealed an inverse behavior. The usefulness of electrophoresis, hematocrit and mean erythrocyte diameter in the diagnosis of canine Ehrlichiosis is discussed. On the base of the results obtained, a series of recommendations are proposed that include: a) consider the use of electrophoresis to evaluate the health status of animals and subclinical processes, b) use the proteinogram for the control and follow-up of patients positive to Ehrlichia canis in order to adopting decisions regarding the therapy to be indicated, c) perform electrophoretic studies in coinfections or other haemoparasitic diseases, d) use of the Hematocrit as a routine parameter to be considered in clinical practice when evaluating canine patients with suspected Ehrlichiosis and e) and continue this line of research including carrying out a complete blood count and blood biochemistry in order to have a systemic view of the state of the disease in patients who come to a veterinary consultation.
La ehrlichiosis canina, es una enfermedad transmitida por garrapatas, causada por varias especies de rickettsia (Rickettsiae) pertenecientes al género Ehrlichia, que incluyen a E. canis, E. ewingii y E. chaffeensis. Debido a que la enfermedad generalmente es asintomática (Fase subclínica) constituye un factor epidemiológico importante para la diseminación de la infección. Existen varias técnicas para el diagnóstico de Ehrlichiosis se incluyen la inmunofluorescencia indirecta (IFI), ELISA, frotis directo, cromatografía en capa sólida y la reacción en cadena de la polimerasa (PCR) siendo el método de ELISA y el frotis directo, los más empleados la clínica veterinaria. Este trabajo plantea la posibilidad de usar una variación de la técnica de electroforesis en gel con tampones de fácil obtención y que tengan una buena resolución de las fracciones proteicas del suero para el diagnóstico de la Ehrlichiosis canina, en combinación con la determinación de otros parámetros como el Hematocrito y el diámetro medio de los eritrocitos. El análisis de 31 perros que acudieron a consulta en la Clínica Docente de Especialidades Veterinarias UTMACH a los cuales se le realizó una prueba rápida con el kit comercial SensPERT Ehrlichia canis Ab permitió identificar 19 animales seropositivos y 12 seronegativos. El análisis de frotis de capa blanca, sólo confirmó la presencia de mórulas en el 31.82 % de los individuos seropositivos. Los perros seropositivos presentaron valores de hematocrito menores y una marcada macrocitosis evidenciada a partir del análisis del diámetro medio de los eritrocitos. La concentración de proteínas totales y globulinas totales fue mayor en los perros seropositivos, mientras que para la concentración de Albúmina cuantificada por el método de Verde de bromocresol, no fueron detectadas diferencias estadísticas entre perros seropositivos y seronegativos. La electroforesis en gel de agarosa y posterior análisis de los densitogramas respectivos permitió establecer hipoalbuminemia e incrementos evidentes en la fracción de las gammaglobulinas, en los caninos seropositivos. Cuando la fracción de Albúmina fue analizada a partir de los datos densitométricos obtenidos del fraccionamiento electroforético en gel de agarosa, las diferencias estadísticas fueron significativas revelando una condición de hipoalbuminemia en perros seropositivos. La relación albúmina/globulinas (A/G) a partir de los datos obtenidos mediante colorimetría fue superior en los perros seropositivos, mientras el análisis densitométrico de las corridas electroforéticas reveló un comportamiento inverso. Se discute la utilidad de la electroforesis, el hematocrito y diámetro medio de los eritrocitos en el diagnóstico de Ehrlichiosis canina. A la luz de los resultados obtenidos se plantean una serie de recomendaciones que incluyen a) considerar el uso de la electroforesis para evaluar el estado sanitario de los animales y procesos subclínicos, b) emplear el proteinograma para el control y seguimiento de los pacientes positivos a Ehrlichia canis a fin de tomar decisiones respecto a la terapia a indicar, c) realizar estudios electroforéticos en coinfecciones u otras enfermedades hemoparasitarias, d) usar el Hematocrito como parámetro de rutina a considerar en la práctica clínica al momento de evaluar pacientes caninos con sospecha de Ehrlichiosis y e) continuar esta línea de investigación incluyendo la realización del hemograma completo y la bioquímica sanguínea a fin de tener una visión sistémica del estado de la enfermedad en los pacientes que llegan a consulta veterinaria.
Keywords: EHRLICHIA; PROTEINOGRAMA; RHIPICEPHALUS; INFECCIÓN